Development of novel self-centering steel coupling beams without beam elongation for earthquake resilience. (1st April 2021) - Wang, Bin; Nishiyama, Minehiro; Zhu, Songye; Tani, Masanori; Jiang, Huanjun
Highlights: A novel seismic-resistant self-centering steel coupling beam is developed. The design is enabled by superelastic SMA bolts and replaceable steel angles. Satisfactory self-centering and energy dissipating capabilities can be achieved. Centerline-rocking behavior eliminates the elongation effect of the coupling beam. The designed coupling beams can realize earthquake resilience in coupled walls. Abstract: Reinforced concrete (RC) coupled walls are extensively used as the seismic-resistant structural system of tall buildings in high seismic zones. In RC coupled wall systems, the coupling beams are typically designed and detailed to dissipate energy through large inelastic responses to meet the expected seismic performance under moderate-to-strong earthquakes. However, costly excessive repair or even complete demolition caused by the considerable damage in conventional RC coupling beams is usually inevitable. Such disadvantage of RC coupling beams has increased the interest on replaceable steel coupling beams, which can isolate the damage concentrated in the fuses; thus, these beams are expected to be replaced after a strong earthquake. However, replacing these beams in practice is difficult if considerable residual deformation exists in these replaceable fuses. Therefore, seismic resilience cannot be explicitly guaranteed. For this reason, this study proposes a novel self-centering (SC) steel coupling beam that incorporates superelastic shape memory alloy (SMA) bolts and steel angles. The SC steel coupling beam is composed of two elastic beam segments and one rocking segment. Elastic beam segments are designed by steel beams that connect to the RC walls at both ends of the coupling beam, whereas the rocking segment located in the middle of the coupling beam is controlled by the SMA bolts and steel angles. Two ingenious shear keys are designed between the elastic beam segments and the rocking segment; these shear keys help the SC coupling beam to exhibit centerline-rocking behavior that is free from beam elongation. The working principle of the novel SC steel coupling beam is described first. Then, the cyclic responses of the SMA bolt and the steel angle, which are the two core components in the SC steel coupling beam, are investigated. The seismic performance of the SC steel coupling beam is computationally investigated in consideration of the effects of steel angles and the prestrain in the SMA bolts. Results show that the proposed SC steel coupling beams exhibit excellent SC capability and energy dissipation. Most damage is isolated in the steel angles, which can be easily and rapidly inspected or replaced after earthquakes without operation interruption. Importantly, beam elongation is almost eliminated under cyclic loading. With these advantages, the SC steel coupling beam can provide a promising solution for high-performance coupled wall systems.